Integrasi Pendidikan Karakter ke dalam Kurikulum Pendidikan Islam Strategi dan Hasil - Aprianti, Astuti; Baiq Uswatun Hasanah; Sulistia Wahyuningsih; Muhammad Sultan Alviqry; Rizky Handayani; Dedi Arman (Jurnal Budi Pekerti Agama Islam, 2024)
The purpose of this writing is to find out the integration of character education into the Islamic education curriculum and learning strategies. The method of this writing using library research method is an approach used to collect information from data from various sources such as articles from the internet and several librarycatalogs this method includes a review of literature searches and documentation that is relevant to the topic of research or certain interests. From the results of thisstudy it can be concluded that the integration of character education into the Islamic education curriculum (Strategy and Results) is very important in developing the moral and ethical values of Islamic education which aims to form a good student personality